2003
DOI: 10.1038/sj.bjc.6600714
|View full text |Cite
|
Sign up to set email alerts
|

Excessive annual BMI increase after chemotherapy among young survivors of testicular cancer

Abstract: Increased body mass index (BMI) is claimed to be a complication among survivors of testicular cancer (TCSs), especially after receiving cisplatin-based chemotherapy. This study compares changes in BMI (kg m À2 ) in TCSs with those observed in age-matched men from the population (controls). Associations between treatment, age and potential BMI changes were sought. In 1999, a survey was performed at the NRH of 444 unilaterally orchiectomised TCSs treated from 1980 to 1990. BMI at survey was recorded in each TCS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Our results from the multivariate regression analysis indicated that in survivors of testicular cancer (TCSs), chemotherapy had an impact on the annual BMI increase independent of age and that the surgery group displayed no significant annual BMI increase (Nord et al, 2003). However, it only explained 8% of our observations as compared to the normal population, thus indicating a multifactorial background for the annual BMI increase.…”
Section: Sirmentioning
confidence: 66%
“…Our results from the multivariate regression analysis indicated that in survivors of testicular cancer (TCSs), chemotherapy had an impact on the annual BMI increase independent of age and that the surgery group displayed no significant annual BMI increase (Nord et al, 2003). However, it only explained 8% of our observations as compared to the normal population, thus indicating a multifactorial background for the annual BMI increase.…”
Section: Sirmentioning
confidence: 66%
“…We read with interest the article of Nord et al (2003) who reported excessive increases in body mass index (BMI) after chemotherapy in long-term survivors of testicular cancer. We believe this study presents important data but do not believe that the data presented fully support the authors' conclusions.…”
Section: Sirmentioning
confidence: 96%
“…After such cytostatic treatment, patients more often had increased serum levels of cholesterol, weight gain, hypertension and decreased renal function (Hansen et al, 1988;Ellis et al, 1992;Raghavan et al, 1992;Bokemeyer et al, 1996;Nord et al, 2003a) than the age-matched general population, or compared to MGCT patients treated by surgery only. Our data support the view of increase of diseases of the circulatory system in patients with MGCT, as our complete cohort of MGCT patients indeed displayed a marginally increased risk of dying from circulatory diseases (SMR: 1.2 (95% CI: 1.0 -1.5)).…”
Section: Discussionmentioning
confidence: 99%
“…1965 1970 1975 1980 1985 1990 1995 2000 1965 1970 1975 1980 1985 1990 1995 One should also discuss alternative and treatment-independent causes leading to cardiovascular events and high-risk factors in testicular cancer survivors. Slight hypogonadism as reduced testosterone serum levels and/or increased LH serum levels are seen in about 15% of these patients (Huddart et al, 2003;Nord et al, 2003a). Hypogonadism may by itself lead to premature ageing with its consequences on disorders of the circulatory system, including increased BMI, serum lipid disturbances and hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation